Checklist and distribution of the Steninae of America north of Mexico (Coleoptera, Staphylinidae) 374. Contribution to the knowledge of Steninae - Puthz, Volker (Zootaxa, 2021)
An up to date checklist of the distribution of North American Steninae is given and new records are documented.